238U, 235U and 234U in seawater and deep-sea corals: A high-precision reappraisal. (1st November 2022) - Kipp, Michael A.; Li, Haoyu; Ellwood, Michael J.; John, Seth G.; Middag, Rob; Adkins, Jess F.; Tissot, François L.H.
Abstract: Uranium isotope ratios are widely utilized in paleoceanography. The 238 U/ 235 U ratio (expressed as δ 238 U) is leveraged as a proxy for the areal extent of anoxic seafloor, and the 234 U/ 238 U ratio (expressed as δ 234 Usec ) tracks riverine and estuarine inputs to the ocean, in addition to featuring prominently in U-series geochronology. Both of these ratios are thought to be recorded by biological carbonates precipitating from seawater, with corals serving as one of the most commonly-used archives of seawater U isotope ratios in the past. The utility of the U isotope proxy in biological carbonate archives relies not only on this faithful archiving of ambient seawater signatures, but also on the homogeneity of the seawater U isotope composition, which enables samples to be leveraged as proxy for the entire ocean. Here we revisit the foundational assumption of homogeneity of the marine U reservoir, and the capacity of deep-sea corals to record the U isotopic composition of ambient seawater. We begin by evaluating the analytical limits of precision and accuracy achievable for both δ 238 U and δ 234 Usec analysis by MC-ICP-MS. We then report data for 45 seawater and 26 deep-sea coral samples from multiple sites around the world. We find subtle δ 238 U and δ 234 Usec heterogeneity that correlates with U concentrations, which allows us to calculate new salinity-normalized global mean seawater values for δ 238 U (−0.379 ± 0.023 ‰) and δ 234 Usec (+145.55 ± 0.28 ‰). At each site, biological carbonates act as precise archives of the seawater δ 238 U value. The same is true for δ 234 Usec, with a few exceptions where samples appear to show vital effects that cause intra-sample 234 U/ 238 U re-partitioning. In sum, these observations support deep-sea corals as a robust archive of seawater U isotope ratios, but highlight the importance of utilizing multiple sample sites and replicate analyses to overcome coral vital effects (for δ 234 Usec ) and subtle marine U isotopic heterogeneity.